How Product Quality, Price and Service Quality Impact Customer Satisfaction? Case Study at Son Hajisony Meatball - Erlina Rufaidah (FKIP Universitas Lampung, 2022)
Customer satisfaction is assessed after transaction or as a result of a comparison between what is felt and what is hoped. Customer satisfaction can thus be used to evaluate a company's future prospects based on how well or poorly it is currently performing. The effect of product quality, price, and service quality perspectives on customer satisfaction at Bakso Son Hajisony during the COVID-19 pandemic will be studied in this study. The results of the descriptive verification approach were examined using the ex post facto methodology and surveys in this study. 75 respondents were used to test the hypotheses using simple linear regression and multiple linear regression. Product quality, price and service quality all have significant effect on customer satisfaction according to the data. Keywords: Customer Satisfaction, Meatball, Price, Product quality, Service quality